The effect of nano-additives in natural ester dielectric liquids: a comprehensive review on stability and thermal properties - Farade, Rizwan A.; Wahab, Noor Izzri Abdul; Mansour, Diaa-Eldin A. (Institute of Electrical and Electronics Engineers, 2023)
Many experimental studies were conducted by various researchers using vegetable oils as transformer oil alternatives. The use of these vegetable oils as dielectric oils for transformers has the potential to minimize the environmental effect of other conventional oils since vegetable oils are biodegradable. In addition, present-day mineral oils are derived from petroleum products; thus, mineral oils will inevitably run out in the future, and major shortages may occur. So, vegetable oils can be the potential candidates to replace mineral oils in the future for transformer applications. Also, these can be potential candidates in heat transfer applications, capacitors, cables, circuit breakers, and tap changers. Vegetable oils are mainly natural esters extracted from natural products. Natural esters are more economical than synthetic esters and sometimes exist naturally in large quantities in certain countries. To get enhanced dielectric properties of natural ester dielectric liquids, many studies propose using nano-additives to form what are called nanofluids. This comprehensive review presents the effect of nano-additives on the ac, dc, and impulse breakdown voltage, dielectric constant, and dissipation factor of natural ester dielectric liquids. The results obtained by various researchers on the dielectric properties of these oils are discussed, as well as clarified physical mechanisms, along with future research prospects.